Downregulation of miR-654-3p in Colorectal Cancer Indicates Poor Prognosis and Promotes Cell Proliferation and Invasion by Targeting SRC - Zhang, Haoran; Shen, Zhanlong; Zhou, Yushi; Zhang, Zhen; Wang, Quan; Zhang, Mengmeng; Jiang, Kewei; Wang, Shan; Ye, Yingjiang; Wang, Bo (Frontiers in Genetics, 2020)
Background: MicroRNAs (miRNAs), such as miR-654-3p, regulate gene expression at the post-transcriptional level affecting malignant tumor behavior. However, the expression levels, function, and mechanism of miR-654-3p in colorectal cancer (CRC) are unknown. Methods: The expression levels of miR-654-3p and SRC in 103 CRC tissues and matched normal colorectal tissues were detected by a quantitative real-time polymerase chain reaction (qRT-PCR). miR-654-3p was overexpressed by RNA mimics and SRC knockdown by siRNA. Function-based experiments were carried out to detect the proliferation and migration abilities in CRC cell lines. Flow cytometry assay was performed to evaluate the effect of miR-654-3p on cell apoptosis and cycle distribution. Xenograft tumor models in nude mice were utilized to evaluate miR-654-3p functions in vivo. Dual-fluorescence reporter assay was used to verify the direct binding between miR-654-3p and SRC. Results: miR-654-3p was downregulated in CRC tissues as compared to matched normal colorectal tissues. The expression levels of miR-654-3p were closely associated with distant metastasis. In addition, elevated expression of miR-654-3p in CRC patients prolonged the overall survival. Upregulated miR-654-3p significantly suppressed the proliferation and migration capacity of CRC cells by enhancing apoptosis and promoting G0/G1 phase arrest. The direct binding between miR-654-3p and SRC was verified by the dual‑luciferase reporter gene. Furthermore, the suppression of proliferation and migration capacity by elevated miR-654-3p level could be reversed by overexpressing SRC. Conclusion: miR-654-3p acts as a tumor suppressor through regulating SRC. It might also serve as a diagnostic and prognostic indicator and a novel molecular target for CRC therapy.